2017
DOI: 10.1093/infdis/jix235
|View full text |Cite
|
Sign up to set email alerts
|

IFITM3, TLR3, and CD55 Gene SNPs and Cumulative Genetic Risks for Severe Outcomes in Chinese Patients With H7N9/H1N1pdm09 Influenza

Abstract: Host genetic factors may influence clinical outcomes of avian and pandemic influenza infections. Such findings have important implications on disease burden and patient care in at-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 44 publications
(111 reference statements)
5
64
0
2
Order By: Relevance
“…In addition, the CC genotype was estimated to confer a six-fold increased risk for severe infection than the CT and TT genotypes [120], reinforcing the idea that IFITM3 is a factor affecting human IAV disease [121]. In another study, over-representation of the IFITM3 CC genotype was detected among fatal cases of Chinese patients infected with IAV pH1N1 and H7N9 viruses [100], and in a more general study, including twelve studies published before February 2018 with more than 16,000 subjects, revealed increased risk of severe influenza in both the East Asian and White populations in the subjects encoding the IFITM3 CC genotype [122].…”
Section: Snps In Host Genes Affecting Iav Diseasementioning
confidence: 80%
See 3 more Smart Citations
“…In addition, the CC genotype was estimated to confer a six-fold increased risk for severe infection than the CT and TT genotypes [120], reinforcing the idea that IFITM3 is a factor affecting human IAV disease [121]. In another study, over-representation of the IFITM3 CC genotype was detected among fatal cases of Chinese patients infected with IAV pH1N1 and H7N9 viruses [100], and in a more general study, including twelve studies published before February 2018 with more than 16,000 subjects, revealed increased risk of severe influenza in both the East Asian and White populations in the subjects encoding the IFITM3 CC genotype [122].…”
Section: Snps In Host Genes Affecting Iav Diseasementioning
confidence: 80%
“…Therefore, patients who carry the T/T genotype may have more robust complement activation during IAV infection, resulting in enhanced inflammation and disease severity [47,79]. According to these results, the polymorphism rs2564978 in gene CD55 was linked to disease severity in adult Chinese cases of avian (H7N9) and human pH1N1 IAV in another study [100]. However, these findings need to be confirmed in bigger cohorts.…”
Section: Snps In Host Genes Affecting Iav Diseasementioning
confidence: 90%
See 2 more Smart Citations
“…Our current knowledge is limited with respect to possible mechanisms underlying severe outcomes with influenza infection . Standardized scoring systems will be key to the identification of virus and host factors related to severe outcomes . Validated biomarkers predicting severity will assist future physicians in tailoring therapies to their patients’ individual needs.…”
Section: Discussionmentioning
confidence: 99%